Perceptions of How Integrated Care Impacts Treatment in Rural Settings - Dawn Graham; Samantha Nandyal; Salonas Ayad (Ohio Journal of Public Health, 2022)
<p class="Paragraph SCXW145727750 BCX2" style="font-weight: normal; font-style: normal; vertical-align: baseline; background-color: transparent; color: windowtext; text-align: left; margin-left: 0px; margin-right: 0px; padding-left: 0px; padding-right: 0px; text-indent: 0px;">Background: In light of the changing face of health care, it is important that practitioners and researchers begin to think strategically regarding comprehensive and accessible care. The purpose of this research study is to provide a deeper understanding of change among health care providers who work on multidisciplinary teams and the impact on patient outcomes. <p class="Paragraph SCXW145727750 BCX2" style="font-weight: normal; font-style: normal; vertical-align: baseline; background-color: transparent; color: windowtext; text-align: left; margin-left: 0px; margin-right: 0px; padding-left: 0px; padding-right: 0px; text-indent: 0px;">Methods: This research was designed as an exploratory phenomenological research study. The experience of interest was how providers described changes in care when working in an integrated care context. Eight semistructured in-depth interviews were conducted with physicians, nurse practitioners, social workers, and psychologists from locations in Southern Ohio, Central Maine, and Eastern Tennessee. Data were analyzed using qualitative coding to find patterns with and across participants associated with their perceptions of health integration. <p class="Paragraph SCXW145727750 BCX2" style="font-weight: normal; font-style: normal; vertical-align: baseline; background-color: transparent; color: windowtext; text-align: left; margin-left: 0px; margin-right: 0px; padding-left: 0px; padding-right: 0px; text-indent: 0px;">Results: Final developed themes described provider perceptions of working in an integrated care environment, and included access to care, interprofessional education, communication between providers. <p class="Paragraph SCXW145727750 BCX2" style="font-weight: normal; font-style: normal; vertical-align: baseline; background-color: transparent; color: windowtext; text-align: left; margin-left: 0px; margin-right: 0px; padding-left: 0px; padding-right: 0px; text-indent: 0px;">Conclusion: Through interviews and a review of the literature, we have found that as integrated care is employed throughout the country, patients have better health outcomes and providers experience efficient and effective work environments. Providers have adapted to the changing environment of integrative medicine; through this study we see that these changes have been for the benefit of the patients. Patients who disproportionately suffer from a lack of health care resources, such as those in rural areas, may benefit greatly from an integrated care model.
Keywords: Integrated health care; Qualitative methods; Interview research; Behavioral health